Barbara Andress: Her career and contributions to early childhood music education. - Harriott, Janette Donovan. (My University, 1999)
Barbara Andress is an internationally known music educator, author, artist, designer of early childhood materials and instruments, clinician, and organizational leader who has dedicated nearly 50 years of her life to music education. Since the late 1960s, Barbara Andress's attention has been on early childhood music education. Her contributions during the second half of the 20th century focused national attention on the importance of music in early childhood.

The purpose of this study was to examine and chronicle the career and professional contributions of Barbara Andress to early childhood music education in the United States. The study documented a biographical summary of her professional life, clarified her responses to selected issues and challenges in the early childhood music education movement, and chronicled her professional contributions as a major figure in the early childhood music education movement.

This study is divided into seven chapters, a bibliography, and nine appendices. Chapter one is the introduction, which includes the purpose, need for the study, organization, procedures, and the limitations of the study. Chapter two is a discussion of the related literature. Chapter three reviews her work as a music educator. Also in chapter three are summaries of her early musical influences and education, her philosophy of music education, and her views on success as a music educator of young children. Chapters four and five detail her music activities and contributions in Arizona and at the national level, respectively. Chapter six summarizes Barbara Andress's views on selected issues and challenges in early childhood music education and presents comments and responses from her colleagues. Chapter seven includes the conclusions and recommendations for further study.

Following the bibliography, appendices provide a list of her publications and writings, a chronology of her life and professional activities, topics for scholarly presentations, all known scholarly presentations, the interview questions for Andress, the cover letter and questionnaire for the colleagues of Andress, Barbara Andress's Nine Point Credo for early childhood music education, MENC's Position Statement on early childhood music education, and selected photos from Barbara Andress's career.
Keywords: Education, History of.; Education, Music.; Biography.; Andress, Barbara.; Music education Study and teaching (Early childhood); Education, Early Childhood.